Analysis of Mathematics Learning Results of Class VII-3 Students at SMP Negeri 3 Kisaran in View of Gender for the 2023/2024 Academic Year - Sirait, Paisal; Rahmadani, Elfira; Masithoh, Ety (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research aims to determine the mathematics learning outcomes of class VII-3 students at SMP Negeri 3 Kisaran and the mathematics learning outcomes of class VII-3 students at SMP Negeri 3 Kisaran in terms of gender. This type of research is descriptive research with data collection using qualitative and quantitative data. This research was carried out at SMP Negeri 3 Kisaran for the 2023/2024 academic year. The research subjects consisted of 1 class with 32 students. The data analysis technique uses descriptive analysis. Based on the research results, it was concluded that mathematics learning outcomes in terms of gender in class VII-3 students at SMP Negeri 3 Kisaran, 16 male students obtained an average score of 29,375, while female students obtained an average score of 29,375. 31.6875. Female students are categorized as superior in learning outcomes for completing final semester exam questions compared to male students.